A novel quantitative trait loci for fusarium head blight resistance in wheat chromosome 7A - Jayatilake, Dimanthi (Kansas State University, 2010)
Fusarium head blight (FHB), caused by Fusarium graminearum, is an important cereal disease in humid and semi-humid wheat growing regions. In recent FHB epidemics in the USA, FHB dramatically reduced wheat yields and grain quality due to mycotoxin contamination. Five types of FHB resistance have been reported, but resistance to disease spread within a spike (Type II) and low deoxynivalenol (DON) accumulation in infected kernels (Type III) have drawn the most attention. A Chinese Spring-Sumai3 chromosome 7A substitution line (CS-SM3-7ADSL) was reported to have a high level of Type II resistance, but quantitative trait locus (QTL) on chromosome 7A has never been mapped. To characterize QTL on chromosome 7A, we developed 191 Chinese Spring-Sumai3-7A chromosome recombinant inbred lines (CRIL) from a cross between Chinese Spring and CS-SM3-7ADSL and evaluated the CRIL in a greenhouse for both types of resistance in three experiments. Two major QTL with Sumai 3 (SM3) origin, conditioning Type II and Type III resistance were mapped in chromosomes 3BS and 7AC. QTL on chromosome 3BS corresponds to Fhb1, previously reported from SM3, whereas 7AC QTL, designated as Fhb5, is a novel QTL identified from SM3 in this study. Fhb5 explains 22% phenotypic variation for Type II resistance and 24% for Type III resistance. Marker Xwmc17 is the closest marker to Fhb5 for both types of resistance. Fhb1 and Fhb5 were additive and together explained 56% variation for Type II and 41% for Type III resistance and resulted in 66% reduction in FHB severity and 84% in DON content. Both QTL showed significant pleiotropy effects on Type II and Type III resistance, suggesting both types of resistance may be controlled by the same gene(s). Haplotype analysis of SM3’s parents revealed that Fhb5 originated from Funo, an Italian cultivar. A survey of worldwide germplasm collection of 400 accessions showed that Fhb5 is present mainly in Chinese cultivars, especially in Funo-related accessions. Further, Fhb5 is the second major QTL from SM3 and have potential to be used in improving wheat cultivars for both types of resistance.
Keywords: Quantitative trait loci mapping; Chromosome recombinant inbred lines; Fusarium head blight; Agriculture, Agronomy (0285)